Knowledge of Healthcare Providers toward New Corona Virus at Directorate of Military Medical Affairs Units - Muhammed Hussein Ali; Wasnaa Jomaa Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Coronavirus is a rapidly spreading disease also known as COVID-19. The epidemic is causedby a new human coronavirus, previously known as (SARS-COV-2), new coronavirus disease it first appearedin December 2019 among patients who had symptoms of viral pneumonia in Wuhan, China. This study aimsto determine healthcare providers’ knowledge related to coronavirus.Methods: A descriptive design is carried throughout the present study Directorate of Military Medical AffairsUnits (Al- Muthanna Military Hospital, Al-Hussein military Hospital, Al-Shaheed Mubder Military Clinic,Al-Naser Military Clinic, Military Medical School) for the period from January 28th, 2021 to February25th, 2021. The study included a non-probability “purposive” sample of (223) health care providers. Thequestionnaire encompasses two main parts (Health Care Providers Socio-Demographic Characteristics, andHealth Care Providers’ knowledge’s Tool).Data were analyzed using the statistical package for social science. The descriptive statistical measures offrequency, percent, mean, Relative Sufficiency, Percentile Grand Mean of Score, Percentile Global Mean ofScore, Pooled Standard Deviation, and Grand/or Global Relative range, standard deviation, and inferentialstatistical measures of T-test, Chi-Square test, Binomial test, Mann-Whitney test, Contingency Coefficientstest, and Wilcoxon Signed Ranks test.Results: The study results showed that half of the study participants depend on their information about thestudied diseases on the “Center for Disease Control of the World Health Organization”, then 158 (70.9%)depend on government websites and official media, then 109 (48.9%) depend on news media about 148(66.4%) rely on Social media. About 26(11.7%) rely on Journals” only.Conclusion: The researchers concluded that the overall evaluation of healthcare providers’ knowledge ismoderate. Recommendation: The researchers recommend that there is a need to conduct further studies on largersample at the national level with the need for an educational program to increase the knowledge of healthcare providers about Corona virus in military medicine.